Automation of Management of Energy Efficient Ventilation Systems (Texas Journal of Multidisciplinary Studies, 2022)
Ventilation with air recirculation is a system where part of the air taken from the room is mixed with cold outside air, heated to the required temperature and then fed into the room. This system can be used only if the air coming from the room does not contain harmful substances and toxic impurities. Whereas the volume of outdoor air in this mixture must comply with all sanitary and hygienic standards, and must not be less than the value of the sanitary standard provided for this type of room.